Hollow Gaussian beams with the power-exponent-phase vortex. Issue 19 (11th November 2018) - Zhou, Guoquan; Zhou, Yimin; Ji, Zhiyue; Chen, Ruipin
ABSTRACT: A kind of hollow Gaussian beams with the power-exponent-phase vortex is introduced. Based on the Collins integral, an analytical expression of a hollow Gaussian beam with the power-exponent-phase vortex passing through a paraxial optical system described by the ABCD matrix approach is derived. The analytical expressions for the beam propagation factors and the orbital angular momentum density of such hollow vortex Gaussian beam passing through a paraxial optical system described by the ABCD matrix approach are also derived, respectively. As a numerical example, the propagation properties of a hollow Gaussian beam with the power-exponent-phase vortex are demonstrated in free space. The evolutions of the normalized intensity, the phase and the orbital angular momentum density distributions are investigated, respectively. The influences of the power order and the topological charge on the beam propagation factors in the x - and y -directions are analysed. The introduced hollow Gaussian beam has potential applications in the atom manipulation and the optical trapping.